Composition and structure of carob (Ceratonia siliqua L.) germ proteins - Bengoechea, C. (2008)
This study was focused on the analysis of the chemical composition of defatted carob germ flour and the protein isolate. The amino acid composition and the nature of the subunits that compose carob germ proteins were also studied. Isolate was obtained by alkaline extraction followed by isoelectric precipitation of proteins. Results showed that an isolate of 96.5% of protein content was obtained. A high amount of amino acids like glutamic acid, aspartic acid and arginine was detected. Carob proteins were found to be composed by aggregates formed by a 131 and 70 kDa subunits linked by non-covalent bonds, and other peptides strongly bounded by disulfide interactions. Both, aggregates and subunits were formed mainly by 100 and 48 kDa monomers linked by disulfide bonds. A considerable content of high molecular mass peptides (HMWP) strongly bounded were also found. Proteins became partially denatured and thermally stabilized at acid pH (pH 2). These results could be useful in the study of different functional properties of carob germ proteins, and the application of these proteins as nutritional ingredients in formulated food.